Self-adaptive active regeneration zinc negative electrode-electrolyte interface stabilization method

By using intelligent polymer additives that can respond to pH changes in the zinc negative electrode-electrolyte interface, the active regeneration and stability of the zinc negative electrode-electrolyte interface is achieved, and the side reaction problems caused by dynamic interface changes are solved and the cycle life of the battery is extended.

CN119812514AActive Publication Date: 2025-04-11GUANGXI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510144145.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The zinc negative electrode-electrolyte interface changes dynamically during the battery cycle, resulting in an accumulated interface side reaction effect and shortening the battery cycle life.

Method used

Using intelligent polymer additives that can respond to pH changes in the electrode-electrolyte interface, the active regeneration and stability of the zinc negative electrode-electrolyte interface is achieved through cross-linking and dissociation of the acyl hydrazone bond.

Benefits of technology

Effectively inhibit the side reaction of zinc negative electrode and the growth of zinc dendrites, stabilize the interface for a long time and sustainable manner, and extend the battery cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812514A_ABST
    Figure CN119812514A_ABST
Patent Text Reader

Abstract

The invention discloses a self-adaptive active regenerated zinc negative electrode-electrolyte interface stabilization method, and relates to the technical field of aqueous zinc ion batteries, and the method is characterized in that the method realizes zinc negative electrode-electrolyte interface stabilization through intelligent macromolecules capable of responding to pH change at an electrode-electrolyte interface to perform crosslinking and dissociation; the preparation process of the intelligent polymer comprises the following steps: respectively preparing hydrazide functionalized polyaspartic acid and aldehyde functionalized polyaspartic acid, and compounding the hydrazide functionalized polyaspartic acid and the aldehyde functionalized polyaspartic acid to obtain the intelligent polymer electrolyte additive. The method can effectively inhibit zinc negative electrode side reaction and zinc dendrite growth. And meanwhile, the problem of dynamic change of a zinc negative electrode-electrolyte interface can be treated in a targeted manner, and the intelligent protection layer can be actively dissociated and regenerated along with charging and discharging circulation of the battery, so that interface parasitic side reaction and zinc dendrite growth can be inhibited for a long time and continuously, and conformal integrity of the interface is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and more specifically to a method for stabilizing an interface of an adaptive active regenerative zinc negative electrode and an electrolyte. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) have the advantages of high safety, low cost, environmental friendliness and high energy density. However, the poor stability of the zinc anode-electrolyte interface can easily lead to serious parasitic side reactions at the interface and uncontrollable zinc dendrite growth, limiting its practical application. One of the key issues of the poor stability of the zinc anode-electrolyte interface is the dynamic nature of the interface. That is, during the battery cycle, zinc is repeatedly deposited and stripped, the surface of the zinc anode is repeatedly expanded and contracted, and zinc dendrites are continuously formed and ablated, resulting in periodic changes in the zinc anode-electrolyte interface environment and continuous interface renewal. This dynamic nature can lead to serious cumulative effects of interfacial side reactions and shorten the battery cycle life. Therefore, how to stabilize the dynamically changing interface between the zinc anode and the electrolyte for a long time and efficiently is a difficult problem that must be solved to achieve the commercial application of AZIBs.

[0003] The stability of the zinc anode-electrolyte interface is affected by both the zinc anode and the electrolyte. The existing methods for stabilizing the zinc anode are "static" methods such as interface modification, electrolyte additives, solid electrolytes, artificial interface protective layers, and construction of structured zinc anodes. Compared with the "static" method, "dynamic" strategies such as self-healing protective layers or self-healing electrolytes are also currently mentioned. However, the self-healing method is a "passive repair" process, that is, "remediation" is carried out after the interface problem occurs. After the battery has undergone a long cycle, the cumulative effect of interface instability factors will still appear, resulting in increasingly uneven components of the protective layer, affecting the battery life. Summary of the invention

[0004] The present invention focuses on the dynamics of the zinc cathode-electrolyte interface, uses an intelligent polymer additive that can respond to pH changes at the electrode-electrolyte interface to perform reversible sol-gel conversion, and develops a new method for stabilizing the zinc cathode-electrolyte interface that can adaptively "actively regenerate". The intelligent interface stabilization method developed by the present invention that can respond to pH changes at the zinc cathode-electrolyte interface and perform "active dissociation and regeneration" along with the battery charge and discharge cycle is a new "active regeneration" method. Compared with "static" or "passive self-repairing" interface stabilization methods, it has more advantages in stabilizing the dynamically changing zinc cathode-electrolyte interface.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions: an adaptive active regeneration zinc negative electrode-electrolyte interface stabilization method, the method achieves zinc negative electrode-electrolyte interface stabilization through a smart polymer that can cross-link and dissociate in response to pH changes at the electrode-electrolyte interface;

[0006] The preparation process of the smart polymer is as follows: hydrazide functionalized polyaspartic acid and aldehyde or ketone functionalized polyaspartic acid are prepared separately, and then the two are compounded as a smart polymer electrolyte additive.

[0007] The present invention is further configured as follows: the smart polymer has a pH-responsive dynamic covalent acylhydrazone bond.

[0008] The present invention is further configured as follows: the hydrazide functionalized polyaspartic acid is prepared from commercial polysuccinimide of different molecular weights as raw materials, polysuccinimide is partially ring-opened using hydrazine hydrate, and the remaining succinimide ring units are subjected to alkaline hydrolysis to prepare hydrazide functionalized polyaspartic acid with different grafting rates. The preparation flow chart thereof is as follows:

[0009]

[0010] The present invention is further configured as follows: the synthesis step of the aldehyde functionalized polyaspartic acid is similar to that of the hydrazide functionalized polyaspartic acid, and the specific process is as follows:

[0011]

[0012] In summary, the present invention has the following beneficial effects: the method can effectively inhibit zinc negative electrode side reactions and zinc dendrite growth. At the same time, the present invention can specifically deal with the problem of dynamic changes in the zinc negative electrode / electrolyte interface, and the intelligent protective layer can "actively dissociate and regenerate" along with the battery charge and discharge cycle, thereby permanently and sustainably inhibiting interface parasitic side reactions and zinc dendrite growth, and maintaining interface conformal integrity. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of the method provided by the present invention;

[0014] Figure 2 It is the zinc deintercalation stability data tested by assembling the Zn / / Zn symmetrical battery in Example 2 of the present invention;

[0015] Figure 3 This is the stability data of zinc intercalation and deintercalation tested in the assembled Zn / / Zn symmetric battery in Example 4 of the present invention. DETAILED DESCRIPTION

[0016] The following is combined with Figure 1-3 The present invention is described in further detail.

[0017] Embodiment 1: A method for adaptively actively regenerating the zinc anode-electrolyte interface stabilization, the method realizing the zinc anode-electrolyte interface stabilization through a smart polymer that can crosslink and dissociate in response to pH changes; the preparation process of the smart polymer is as follows: hydrazide functionalized polyaspartic acid and aldehyde or ketone functionalized polyaspartic acid are prepared separately, and then the two are compounded as a smart polymer electrolyte additive. The smart polymer has a pH-responsive dynamic covalent acylhydrazone bond.

[0018] The hydrazide functionalized polyaspartic acid is prepared from commercial polysuccinimide of different molecular weights as raw materials, polysuccinimide is partially ring-opened with hydrazine hydrate, and the remaining succinimide ring units are subjected to alkaline hydrolysis to prepare hydrazide functionalized polyaspartic acid with different grafting rates. The preparation flow chart is as follows:

[0019]

[0020] The synthesis steps of the aldehyde functionalized polyaspartic acid are similar to those of the hydrazide functionalized polyaspartic acid. Taking the partially ring-opened polysuccinimide using 4-aminobenzaldehyde as an example, the preparation flow chart is as follows:

[0021]

[0022] When the pH of the interface increases, acylhydrazone bonds are generated, and the PASP molecular chains are cross-linked in situ to form a smart gel protective layer. The molecular structure of the acylhydrazone cross-linked PASP gel is as follows:

[0023]

[0024] The above method can effectively inhibit zinc negative electrode side reactions and zinc dendrite growth. At the same time, the present invention can specifically deal with the problem of dynamic changes in the zinc negative electrode-electrolyte interface. The intelligent protective layer can "actively dissociate and regenerate" along with the battery charge and discharge cycle, thereby permanently and sustainably inhibiting interface parasitic side reactions and zinc dendrite growth, and maintaining interface conformal integrity.

[0025] Example 2

[0026] 1. Synthesis of hydrazide functionalized polyaspartic acid by ring opening of hydrazine hydrate:

[0027] The ring-opening reaction of polysuccinimide was used to prepare hydrazide-functionalized polyaspartic acid opened with hydrazine hydrate. First, 1 g of polysuccinimide was dispersed in 10 mL of water at 50 ° C to obtain a uniform suspension. 10 mL of hydrazine hydrate aqueous solution (0.5306 g, 10.38 mmol) was added dropwise to the system and reacted at 50 ° C for 12 h. The reaction solution was poured into a dialysis bag and dialyzed in deionized water for three days, during which the deionized water was continuously replaced. Finally, the dialyzed aqueous solution was freeze-dried to obtain hydrazide-functionalized polyaspartic acid.

[0028] 2. Synthesis of aldehyde functionalized polyaspartic acid from 4-aminobenzaldehyde:

[0029] 2 g of polysuccinimide was dispersed in 20 mL of water at 50 ° C to obtain a uniform suspension. Then, an aqueous solution of 4-aminobenzaldehyde (3.08907 g, 25.5 mmol) was added dropwise to the system under stirring, and the reaction was carried out at 70 ° C for 12 h under nitrogen protection. The reaction solution was poured into a dialysis bag and dialyzed in deionized water for three days, during which the deionized water was continuously replaced. Finally, the dialyzed aqueous solution was freeze-dried to obtain aldehyde-functionalized polyaspartic acid.

[0030] 3. Compounding as smart polymer electrolyte additives:

[0031] The two modified polyaspartic acids synthesized above were compounded at a molar ratio of 1:1 and added into an aqueous zinc ion battery electrolyte (the electrolyte formula was a 2M ZnSO4 aqueous solution), and the total amount of the compounded additives added was 5 mg / mL.

[0032] 4. Stability data of zinc intercalation and deintercalation tested by assembling Zn / / Zn symmetrical cells:

[0033] Using Whatman, GF / D glass fiber film as the battery separator, assembling CR2032 button battery, the test data is as follows Figure 2 shown.

[0034] Test conditions: Current density: 5 mA cm -2 , zinc deintercalation capacity: 2.5 mAh cm -2

[0035] Example 3

[0036] 1. Synthesis of hydrazide functionalized polyaspartic acid by ring opening of hydrazine hydrate:

[0037] The ring-opening reaction of polysuccinimide was used to prepare hydrazide-functionalized polyaspartic acid opened with hydrazine hydrate. First, 1 g of polysuccinimide was dispersed in 10 mL of water at 50 ° C to obtain a uniform suspension. 10 mL of hydrazine hydrate aqueous solution (0.5306 g, 10.38 mmol) was added dropwise to the system and reacted at 50 ° C for 12 h. The reaction solution was poured into a dialysis bag and dialyzed in deionized water for three days, during which the deionized water was continuously replaced. Finally, the dialyzed aqueous solution was freeze-dried to obtain hydrazide-functionalized polyaspartic acid.

[0038] 2. 3-amino-1,2-propanediol is ring-opened to prepare hydroxyl-functionalized polyaspartic acid, and then hydroxyl-oxidized to synthesize aldehyde-functionalized polyaspartic acid:

[0039] 2 g of polysuccinimide was dispersed in 20 mL of water at 50 ° C to obtain a uniform suspension. Then, an aqueous solution of 3-amino-1,2-propanediol (2.3238 g, 25.5 mmol) was added dropwise to the system under stirring and reacted at 50 ° C for 12 h. After that, the reaction solution was poured into a dialysis bag and dialyzed in deionized water for three days, during which the deionized water was continuously replaced. Finally, the dialyzed aqueous solution was freeze-dried to obtain hydroxyl-functionalized polyaspartic acid. 1 g of hydroxyl-functionalized polyaspartic acid was weighed and dissolved in 42 mL of water. Subsequently, sodium periodate (2.6459 g, 12.37 mmol) was added to the reaction solution and reacted in the dark for 30 min. The reaction solution was dialyzed and freeze-dried to obtain aldehyde-functionalized polyaspartic acid.

[0040] 3. Compounding as smart polymer electrolyte additives:

[0041] The two modified polyaspartic acids synthesized above were compounded at a molar ratio of 1:1 and added into an aqueous zinc ion battery electrolyte (the electrolyte formula was a 2M ZnSO4 aqueous solution), and the total amount of the compounded additives added was 5 mg / mL.

[0042] Example 4

[0043] 1. Directly use two commercial catechol derivatives containing hydrazide and aldehyde groups as smart polymer electrolyte additives:

[0044] 3,4-Dihydroxybenzoylhydrazide:

[0045]

[0046] 3,4-Dihydroxybenzaldehyde:

[0047]

[0048] The above two catechol derivative small molecules are compounded at a molar ratio of 1:1 and added into an aqueous zinc ion battery electrolyte (the electrolyte formula is a 2M ZnSO4 aqueous solution), and the total molar concentration of the compounded additive is 5mM.

[0049] The catechol groups in the small molecules of catechol derivatives undergo electrochemical oxidation polymerization in the electrolyte to form oligomer particles, which are suspended in the electrode solution. The surface of the oligomer particles contains hydrazide and aldehyde active groups, which can sense the pH changes of the electrolyte to form acylhydrazone bond crosslinking and acylhydrazone bond cleavage and dissociation.

[0050] 2. Assemble Zn / / Zn symmetric battery and test the stability data of zinc intercalation and deintercalation:

[0051] Using Whatman, GF / D glass fiber film as the battery separator, CR2032 button battery was assembled, and the test results are as follows: Figure 3 shown.

[0052] Test conditions: Current density: 5 mA cm -2 , zinc deintercalation capacity: 2.5 mAh cm -2 .

[0053] Working principle: Smart polymer materials are often prepared by dynamic covalent cross-linking. The dynamic covalent bonds that are currently studied more are imine bonds, disulfide bonds, oxime bonds, acylhydrazone bonds, etc. Among them, acylhydrazone bonds (-CO-NH-N=CH-) are generated by the reaction of ketones or aldehydes with hydrazides, with mild conditions and high yields. Acylhydrazone bonds can exist stably in neutral or alkaline environments, and can undergo reversible rupture or exchange reactions with aldehydes, ketones or hydrazides under weakly acidic conditions (pH≈4). Therefore, acylhydrazone cross-linked polymers usually have self-healing and pH responsiveness. The electrolyte of aqueous zinc ion batteries is a ZnSO4 solution with a molar concentration of 2M. The pH value of the electrolyte is about 4. When side reactions occur in the battery, the interface pH value will increase, and the increase in pH will lead to the generation of zinc negative electrode passivation byproducts, affecting the battery performance. Therefore, the pH value variation range of the zinc negative electrode-electrolyte interface layer of aqueous zinc ion batteries matches the pH response range of acylhydrazone bonds.

[0054] The present invention prepares hydrazide and aldehyde functionalized polyaspartic acid (PASP) respectively, and mixes them as smart polymer electrolyte additives. When the battery is charged, the pH value of the zinc negative electrode / electrolyte interface layer increases, acylhydrazone bonds are generated, and the PASP molecular chains are cross-linked in situ to form a smart gel protective layer. The protective layer can reduce the contact between the negative electrode and water and inhibit parasitic side reactions at the interface. The PASP molecular skeleton contains a large number of amide bonds and zinc-philic carboxyl groups, which can also effectively promote Zn 2+ Desolvation, stabilization of Zn 2+ When the battery is discharged, the pH value of the interface decreases, the acylhydrazone bond breaks, and the gel protective layer dissociates to form a sol that disperses into the electrolyte. The sol state can also regulate the Zn 2+ Solvation structure, stable interface. The smart gel protective layer can "actively dissociate and regenerate" along with the battery charge and discharge cycle, thereby stabilizing the dynamically changing interface.

[0055] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. An adaptive active regeneration zinc negative electrode-electrolyte interface stabilization method, characterized by: The method achieves interfacial stabilization of the zinc negative electrode and the electrolyte by using a smart polymer that can cross-link and dissociate in response to pH changes at the electrode-electrolyte interface; The preparation process of the smart polymer is as follows: hydrazide functionalized polyaspartic acid and aldehyde or ketone functionalized polyaspartic acid are prepared separately, and then the two are compounded as a smart polymer electrolyte additive.

2. The method for stabilizing the interface of an adaptive active regeneration zinc negative electrode and an electrolyte according to claim 1, characterized in that: The smart polymer has a pH-responsive dynamic covalent acylhydrazone bond.

3. The method for stabilizing the interface of an adaptive active regeneration zinc negative electrode and an electrolyte according to claim 1, characterized in that: The hydrazide functionalized polyaspartic acid is prepared from commercial polysuccinimide of different molecular weights as raw materials, polysuccinimide is partially ring-opened with hydrazine hydrate, and the remaining succinimide ring units are subjected to alkaline hydrolysis to prepare hydrazide functionalized polyaspartic acid with different grafting rates. The preparation flow chart is as follows:

4. The method for stabilizing the interface of an adaptive active regeneration zinc negative electrode and an electrolyte according to claim 1, characterized in that: The aldehyde-functionalized polyaspartic acid is prepared from commercial polysuccinimide of different molecular weights as raw materials, using 4-aminobenzaldehyde to partially open the polysuccinimide ring, and the remaining succinimide ring units are subjected to alkaline hydrolysis to prepare aldehyde-functionalized polyaspartic acid with different grafting rates. The preparation flow chart is as follows:

5. The method for stabilizing the interface of an adaptive active regeneration zinc negative electrode and an electrolyte according to claim 1, characterized in that: The hydrazide-based additive component can be provided by hydrazine hydrate, 4-aminobenzohydrazide or other small component modified hydrazide-functionalized polyaspartic acid, or other polymers containing hydrazide groups, or 3,4-dihydroxybenzohydrazide, maleic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, and pyridine-2,6-dicarboxylic acid dihydrazide.

6. The method for stabilizing the interface of an adaptive active regeneration zinc negative electrode and an electrolyte according to claim 1, characterized in that: The aldehyde or ketone additive component can be provided by aldehyde-functionalized polyaspartic acid prepared by modifying 4-aminobenzaldehyde or other small components, or other polymers containing aldehyde groups, or other polymers containing ketone groups such as polydiacetone acrylamide, or small molecule compounds containing aldehyde groups such as 3,4-dihydroxybenzaldehyde, glyoxal, succinaldehyde, adipaldehyde, glutaraldehyde, and suberaldehyde, or 2,5-hexanedione, 2,5-heptanedione, 2,7-octanedione, and 3,6-octanedione.

Citation Information

Patent Citations

  • Dual-network self-healing hydrogel electrolyte, preparation method thereof and aqueous zinc ion battery

    CN117362523A

  • Zinc negative electrode long-acting protective coating with pH response slow release function, preparation method of zinc negative electrode long-acting protective coating and application of zinc negative electrode long-acting protective coating in zinc battery

    CN117936687A

  • Amino acid modified electrolyte for aqueous zinc ion battery and preparation method of amino acid modified electrolyte

    CN118825439A

  • Slim curtain wall system

    KR1020260030360A

  • Method for the preparation of degradable microgel particles, and microgel compositions thereof

    US20160106676A1